The birdcage [videorecording (Blu-Ray)] - Williams, Robin, 1951-2014; Lane, Nathan, 1956-; Hackman, Gene; Wiest, Dianne; Azaria, Hank, 1964-; Flockhart, Calista, 1964-; Futterman, Dan, 1967-; Baranski, Christine; May, Elaine, 1932- ([publisher not identified], 2014)
When the son of a gay man invites his fiancee's ultra-conservative family over for dinner, his father tries to act straight while his partner plays an endearing old woman.